(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The article discusses the role of agro-clusters in poverty reduction in rural areas through business structures, its problems and the existing opportunities of the rural population to reduce poverty in the future. At the same time, opportunities for the development of farms through agro-cluster structures, the possibility of their introduction into the activities of farms and dehkan farms, which are other business structures in agriculture, were considered